2020
DOI: 10.1111/petr.13765
|View full text |Cite
|
Sign up to set email alerts
|

Factors affecting survival in children requiring intensive care after hematopoietic stem cell transplantation. A retrospective single‐center study

Abstract: Allo‐HSCT is associated with life‐threatening complications. Therefore, a considerable number of patients require admission to a PICU. We evaluated the incidence and outcome of PICU admissions after allo‐HSCT in children, along with the potential factors influencing PICU survival. A retrospective chart review of 668 children who underwent first allo‐HSCT in the Department of Pediatric Hematology/Oncology and BMT in Wrocław during years 2005‐2017, particularly focusing on patients admitted to the PICU within 1‐… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
12
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 5 publications
(13 citation statements)
references
References 42 publications
1
12
0
Order By: Relevance
“…The most common PICU admission indications are respiratory failure and septic shock in the study series similar to ours 9,23 . Neurological, renal, and cardiac causes, which are seen as transplant-related acute complications, are mostly seen within the first 100 days 24 …”
Section: Discussionsupporting
confidence: 63%
See 1 more Smart Citation
“…The most common PICU admission indications are respiratory failure and septic shock in the study series similar to ours 9,23 . Neurological, renal, and cardiac causes, which are seen as transplant-related acute complications, are mostly seen within the first 100 days 24 …”
Section: Discussionsupporting
confidence: 63%
“…The length of stay had no impact on mortality in our study. Although some studies found a correlation between mortality and length of stay, there was no such relationship in others 7,15,23,25 …”
Section: Discussionmentioning
confidence: 99%
“…In the pre-engraftment period, high rates of PICU admissions (32%) and deaths due to sepsis (7.4%) were observed. This phenomenon highlights the elevated risk of allo-HSCT complications in the infant population ( 18 ). A mortality of 40.9% was reported before 2009, while 22.2% was observed during 2009–2019; the improvements in survival rates were similar to those in studies reporting only slow progress in this age group ( 1 4 ).…”
Section: Discussionmentioning
confidence: 91%
“…In the preengraftment period, high rates of PICU admissions (32%) and deaths due to sepsis (7.4%) were observed. This phenomenon highlights the elevated risk of allo-HSCT complications in the infant population (18) 2). In this study, the observed phenomena of excessive toxicity and mortality were associated with multiple factors.…”
Section: Discussionmentioning
confidence: 98%
“…HSCT is a successful therapy offering the possibility of a cure for life-threatening conditions; however, it is an intensive treatment with risk of serious complications, significant physical and psychological symptoms, poor quality of life (QoL), and can be lethal [3][4][5][6]. As reported in previous studies, pediatric patients who died following HSCT were often treated in the pediatric intensive care unit (PICU) with invasive treatments during End-of-Life (EOL) [4,[6][7][8]. Of these studies, three showed that pediatric HSCT patients often died from treatment-related complications (60, 68, and 81%) compared to disease-related (40, 32, and 19%) [4,6,8].…”
Section: Introductionmentioning
confidence: 99%